1998
DOI: 10.1007/bf03189327
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of deramciclane (EGIS-3886) in rat brain regions

Abstract: The time related distribution and pharmacokinetics of double-labelled EGIS-3886 (EGIS-3886-phenyl-14C and -ethyl-3H) were studied in the plasma, hypophysis and 14 cerebral regions, including the spinal cord of the rat after a single oral treatment (acute experiments) and after repeated administration of one dose daily for six days (subacute experiments). The tissue levels of EGIS-3886 (deramciclane) were calculated from the simultaneously determined dpm values and the specific activities of the two radioisomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In this study, all three test formulations all exhibited both a peak and a hump. It usually indicated the enterohepatic cycle was involved in oral absorption [23]. However, literatures about the enterohepatic cycling of LCD were not available after investigation.…”
Section: In Vivo Pharmacokineticsmentioning
confidence: 98%
“…In this study, all three test formulations all exhibited both a peak and a hump. It usually indicated the enterohepatic cycle was involved in oral absorption [23]. However, literatures about the enterohepatic cycling of LCD were not available after investigation.…”
Section: In Vivo Pharmacokineticsmentioning
confidence: 98%
“…[5][6][7][8][9][10] The resulting metabolite and derivatives show increased distribution and significant plasma levels for a longer biological half-life than the parent compound. 11,12 Two tritium labelled forms of deramciclane were required with the label in the camphor skeleton, ( [3-3 H]deramciclane (3)) and the side chain ([2-dimethylamino- [2][3] H]ethoxy]deramciclane (9)) for in vitro and in vivo studies to further investigate various aspects of the metabolism and pharmacokinetics of deramciclane. [11][12][13][14][15][16][17][18][19] Previous studies with 3 H and 14 C labelled deramciclane had showed that the metabolism of the camphor skeleton and side chain could be differentiated by virtue of their significantly different biological half-life values.…”
Section: Introductionmentioning
confidence: 99%